Efektivitas Pelvic Floor Muscle Training dan Bladder Training dalam Mengelola Inkontinensia Urine pada Alzheimer: Literature Review - Firmanda, Giovanni Iga; Wahyuningsih, Aries; Pratiwi, Wahyu Nur (PSIK FKKMK UGM, 2024)
Background: Urinary incontinence is a common problem in Alzheimer's patients that significantly affects the quality of life and well-being of the sufferers. Non-pharmacological interventions such as Pelvic Floor Muscle Training (PFMT) and Bladder Training have been considered effective methods in managing this condition, but the cognitive limitations of Alzheimer's patients pose special challenges in their implementation. Objective: This literature review aimed to analyze the effectiveness of PFMT and Bladder Training in managing urinary incontinence in Alzheimer's patients and to understand the challenges and obstacles faced in implementing these interventions. Method: The type of study was a literature search. It was carried out through the EBSCO, Proquest and Science Direct electronic databases that discussed the problem of incontinence in Alzheimer's patients published in 2017-2022. Studies that met the inclusion and exclusion criteria were selected and evaluated using the JBI critical appraisal tool. Results: From the search results, 4 studies met the inclusion criteria and were analyzed in this review. The findings indicated that PFMT and Bladder Training can reduce the frequency of urinary incontinence in elderly with Alzheimer's.Conclusion: PFMT and Bladder Training (BT) play important roles in managing urinary incontinence in Alzheimer's patients. PFMT helps improve pelvic floor muscle control, while BT helps regulate mixed frequency. The combination of these two therapies can provide significant benefits in the management of urinary incontinence in Alzheimer's patients, helping to improve the patient's quality of life and overall well-being.INTISARILatar belakang: Inkontinensia urine merupakan masalah umum pada pasien Alzheimer, yang secara signifikan memengaruhi kualitas hidup dan kesejahteraan penderitanya. Intervensi non-farmakologis seperti Pelvic Floor Muscle Training (PFMT) dan Bladder Training telah dipertimbangkan sebagai metode efektif dalam mengelola kondisi inkontinensia urine ini. Namun, keterbatasan kognitif pada pasien Alzheimer menimbulkan tantangan khusus dalam penerapannya. Tujuan: untuk mengevaluasi efektivitas PFMT dan Bladder Training dalam mengelola inkontinensia urine pada pasien Alzheimer, serta memahami tantangan dan kendala yang dihadapi dalam penerapan intervensi ini. Metode: Jenis penelitian ini adalah pengkajian literatur. Pencarian literatur dilakukan melalui database elektronik EBSCO, Proquest, dan Science Direct, yang membahas masalah inkontinensia pada pasien Alzheimer, terbitan tahun 2017-2022. Literatur yang memenuhi kriteria inklusi, diseleksi dan dievaluasi menggunakan JBI’s critical appraisal tools. Hasil: Dari hasil pencarian, sebanyak 4 literatur memenuhi kriteria inklusi dan dianalisis dalam review ini. Hasil temuan menunjukkan bahwa PFMT dan Bladder Training berpengaruh terhadap pengelolaan inkontinensia urine pada pasien Alzheimer, meningkatkan kontrol otot dan frekuensi miksi, serta meningkatkan kualitas hidup pasien.Simpulan: Pelvic Floor Muscle Training (PFMT) dan Bladder Trainining (BT) dapat mengurangi frekuensi inkontinensia urine pada lansia dengan Alzheimer.